Cement composition and method for producing laminated object
Patent Information
- Application Number
- JP2021060308
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-03-31
Smart Images

Figure 0007652610000001 
Figure 0007652610000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a cement composition and a method for producing a layered object using the cement composition. [Background technology]
[0002] A technology known as photolithography is known in which a layered object (also referred to as an additive manufacturing object in this specification) is produced by curing a liquid photocurable resin, layer by layer, by exposure to ultraviolet light based on digital data for three-dimensional modeling created using CAD or the like. In addition to photolithography, other known technologies for producing additive objects include powder fixation lamination, which produces additive objects by repeatedly performing an inkjet-type operation of adding a binder (liquid for modeling) to powder (e.g., metal powder, plaster powder, etc.) laid out in layers and solidifying it, and fused deposition modeling, which produces additive objects by repeatedly performing an operation of melting a thermoplastic resin at high temperature to form a liquid layer, and then cooling and hardening the layer. The technology for manufacturing additively manufactured objects is sometimes called additive manufacturing. In addition, additive manufacturing devices are sometimes called 3D printers.
[0003] In recent years, attempts have been made to use cement-based materials in the above-mentioned additive manufacturing techniques. For example, Patent Document 1 describes a hydraulic composition for additive manufacturing devices that contains a composite binder containing 2 to 12 parts by mass of polyvinyl alcohol having an average particle size of 110 μm or less, per 100 parts by mass of an inorganic binder (e.g., one containing 50 to 100 mass% calcium aluminates), and sand. Patent Document 2 describes a cement composition for molding containing cement, calcium aluminates, anhydrous gypsum, urea, and a setting retarder, characterized in that, relative to 100 parts by mass of the cement, the amount of the calcium aluminates is 50 to 80 parts by mass, the amount of the anhydrous gypsum is 7 to 28 parts by mass, the amount of the urea is 5 to 23 parts by mass, and the amount of the setting retarder is 0.1 to 5 parts by mass.
[0004] In general, additive manufacturing techniques are suitable for manufacturing objects having thin-walled portions. However, additive manufacturing objects manufactured using a cement composition, which is a hydraulic material containing at least cement and water, have a problem in that the thin-walled portions are easily chipped by external forces.
[0005] On the other hand, it is known that by mixing uniformly dispersed fibers such as steel fibers and organic fibers such as vinylon and polypropylene into cement compositions such as concrete and mortar, the tensile strength, bending strength and shear strength of the hardened product of the resulting cement composition such as concrete or mortar can be improved, and also impact resistance and toughness can be improved, cracks can be suppressed, and spalling can be prevented.
[0006] For this reason, cement compositions containing fibers are being considered as additive manufacturing materials made of cement compositions. For example, Patent Document 3 describes a method for manufacturing a fiber-reinforced concrete member in which the orientation of the fibers can be easily controlled by extruding fiber-reinforced concrete to a predetermined position from the nozzle of an additive manufacturing device.
[0007] However, since Patent Document 3 focuses on controlling the fiber orientation, the material composition of fiber-reinforced concrete, which is the material used in additive manufacturing technology, is not fully examined. For this reason, even if the technology of Patent Document 3 is implemented, problems may arise due to the material composition of the fiber-reinforced concrete. For example, when a cement composition used in an additive manufacturing technique contains fibers, problems may arise when the cement composition is pumped into an additive manufacturing device, such as separation of the fibers from other materials and a shortened pot life, which is the time during which the cement composition retains good fluidity and can be used. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2019-116095 A [Patent Document 2] JP 2020-66549 A [Patent Document 3] JP 2020-2744 A Summary of the Invention [Problem to be solved by the invention]
[0009] The object of the present invention is to provide a cement composition to be used for the production of additive manufacturing objects, which, despite containing fibers, is resistant to the phenomenon in which the fibers and materials other than the fibers separate during pumping (hereinafter, may be referred to as "material separation"), and has a sufficiently long pot life suitable for additive manufacturing. [Means for solving the problem]
[0010] As a result of intensive research into solving the above problems, the present inventors have found that the above object can be achieved by a cement composition containing cement, urea, a set retarder, fine aggregate, fibers, and water, wherein the amount of the urea is 0.5 to 15 parts by mass, the amount of the set retarder is 0.5 to 2.0 parts by mass, the amount of the fine aggregate is 100 to 250 parts by mass, and the amount of the water is 21 to 59 parts by mass, relative to 100 parts by mass of the cement, and the proportion of the fibers in the cement composition is 0.3 to 7.0 vol. % relative to 100 vol. % of the entire cement composition excluding the fibers, and the present invention has been completed.
[0011] Furthermore, the present inventors have found that the above object can be achieved when the cement composition is concrete, that is, when the cement composition contains cement, urea, a set retarder, fine aggregate, coarse aggregate, fiber, and water, by using a cement composition in which the amount of the urea is 0.5 to 15 parts by mass, the amount of the set retarder is 0.5 to 2.0 parts by mass, the amount of the fine aggregate is 40 to 240 parts by mass, the amount of the coarse aggregate is 10 to 210 parts by mass, and the amount of the water is 21 to 59 parts by mass, relative to 100 parts by mass of the cement, and the proportion of the fibers in the cement composition is 0.3 to 7.0% by volume, based on 100% by volume of the entire cement composition excluding the fibers, and thus completed the present invention.
[0012] The present invention provides the following [1] to [5]. [1] A cement composition comprising cement, urea, a set retarder, fine aggregate, fiber, and water, but not containing coarse aggregate, the amount of the urea being 0.5 to 15 parts by mass, the amount of the set retarder being 0.5 to 2.0 parts by mass, the amount of the fine aggregate being 100 to 250 parts by mass, and the amount of the water being 21 to 59 parts by mass, relative to 100 parts by mass of the cement, and the proportion of the fibers in the cement composition being 0.3 to 7.0 vol. % relative to 100 vol. % of the entire cement composition excluding the fibers. [2] A cement composition comprising cement, urea, a set retarder, fine aggregate, coarse aggregate, fiber, and water, wherein the amount of the urea is 0.5 to 15 parts by mass, the amount of the set retarder is 0.5 to 2.0 parts by mass, the amount of the fine aggregate is 40 to 240 parts by mass, the amount of the coarse aggregate is 10 to 210 parts by mass, and the amount of the water is 21 to 59 parts by mass, relative to 100 parts by mass of the cement, and the proportion of the fibers in the cement composition is 0.3 to 7.0 vol. % relative to 100 vol. % of the entire cement composition excluding the fibers. [3] The cement composition according to [1] or [2] above, wherein the cement comprises an ultra-fast hardening cement. [4] The cement composition according to any one of the above [1] to [3], wherein the fibers have a diameter of 0.005 to 1.0 mm, a length of 2 to 30 mm, and an aspect ratio (length / diameter) of 20 to 200. [5] A method for manufacturing an additive manufacturing object using the cement composition according to any one of [1] to [4] above, comprising: a pumping step of pumping the cement composition with a pump and supplying it to an additive manufacturing apparatus; and a modeling step of extruding the cement composition in the additive manufacturing apparatus to perform additive manufacturing layer by layer to produce an additive manufacturing object. Effect of the Invention
[0013] Since the cement composition of the present invention contains fibers, when it is used as a material for producing a layered object including a thin portion, the layered object is less likely to suffer from chipping or the like. Furthermore, despite the inclusion of fibers, the cement composition of the present invention is less susceptible to material separation when pumped from a preparation site of the composition to an additive manufacturing apparatus. Furthermore, the cement compositions of the present invention, despite containing fibers, have a pot life long enough to be suitable for additive manufacturing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] A first embodiment of the cement composition of the present invention is a cement composition containing cement, urea, a set retarder, fine aggregate, fiber, and water, but not containing coarse aggregate, in which the amount of the urea is 0.5 to 15 parts by mass, the amount of the set retarder is 0.5 to 2.0 parts by mass, the amount of the fine aggregate is 100 to 250 parts by mass, and the amount of the water is 21 to 59 parts by mass, relative to 100 parts by mass of the cement, and the proportion of the fibers in the cement composition is 0.3 to 7.0 vol% in total relative to 100 vol% of the entire cement composition excluding the fibers.
[0015] A second embodiment of the cement composition of the present invention is a cement composition comprising cement, urea, a set retarder, fine aggregate, coarse aggregate, fiber, and water, wherein the amount of the urea is 0.5 to 15 parts by mass, the amount of the set retarder is 0.5 to 2.0 parts by mass, the amount of the fine aggregate is 40 to 240 parts by mass, the amount of the coarse aggregate is 10 to 210 parts by mass, and the amount of the water is 21 to 59 parts by mass, relative to 100 parts by mass of the cement, and the proportion of the fibers in the cement composition is 0.3 to 7.0% by volume, based on 100% by volume of the entire cement composition excluding the fibers.
[0016] In the present invention, examples of cement include ultra-fast hardening cement, ultra-fast strength Portland cement, high-early strength Portland cement, ordinary Portland cement, moderate heat Portland cement, low heat Portland cement, white Portland cement, blast furnace cement, fly ash cement, alumina cement, ecocement, etc. These may be used alone or in combination of two or more. Among them, a preferred embodiment includes one containing 30 to 70 mass % of ultra rapid hardening cement from the viewpoint of shortening the manufacturing time of the layered object. When the proportion of the ultra-rapid hardening cement is 30% by mass or more, the efficiency of manufacturing a layered object can be further improved, and when the proportion of the ultra-rapid hardening cement is 70% by mass or less, the material cost can be further reduced.
[0017] Ultra-fast hardening cement is made by mixing Portland cement with a hardening agent made of high alumina cement and gypsum, or with a hardening agent made of amorphous calcium aluminate and gypsum, and calcium fluoroaluminate (C 11 They are broadly divided into two types: those based on compounds such as calcium sulfoaluminate (3CaO·3Al2O3·CaSO4) and calcium sulfoaluminate (3CaO·3Al2O3·CaSO4). In the present invention, either type can be used equally well.
[0018] In the present invention, urea is used to suppress separation of materials in the cement composition and to ensure a sufficiently long pot life of the cement composition. The amount of urea is 0.5 to 15 parts by mass, preferably 0.7 to 10 parts by mass, more preferably 1.0 to 7.0 parts by mass, still more preferably 1.2 to 5.0 parts by mass, and particularly preferably 1.5 to 3.0 parts by mass, relative to 100 parts by mass of cement. If the amount of urea is less than 0.5 parts by mass, separation of the fibers and materials other than the fibers occurs during pumping from the production site of the cement composition to the additive manufacturing device, or the pot life becomes insufficient. Also, if the amount of urea is more than 15 parts by mass, the compressive strength of the additive manufacturing device decreases.
[0019] In the present invention, the set retarder is used to ensure a sufficiently long pot life of the cement composition. Examples of the setting retarder include citric acid and its salts, heptonic acid and its salts, succinic acid and its salts, tartaric acid and its salts, gluconic acid and its salts, malic acid and its salts, and the like. Among these, citric acid is preferred from the viewpoint of extending the pot life. The amount of the set retarder per 100 parts by mass of cement is 0.5 to 2.0 parts by mass, preferably 0.6 to 1.9 parts by mass, more preferably 0.7 to 1.8 parts by mass, and particularly preferably 0.8 to 1.7 parts by mass. If the amount of the retarder is less than 0.5 parts by mass, the working life of the cement composition is shortened, making it difficult to perform additive manufacturing involving pumping. If the amount of the retarder is more than 2.0 parts by mass, material separation is likely to occur.
[0020] In the present invention, the fine aggregate is used to impart good dimensional stability to the shaped object so that the shape of the shaped object does not collapse during stacking. Examples of fine aggregates include crushed limestone sand, silica sand, river sand, mountain sand, land sand, sea sand, slag fine aggregate, lightweight fine aggregate, etc. These may be used alone or in combination of two or more. Among fine aggregates, crushed limestone sand is preferred. In a first embodiment of the cement composition of the present invention that does not contain coarse aggregate, the amount of fine aggregate such as crushed limestone sand per 100 parts by mass of cement is preferably 100 to 250 parts by mass, more preferably 120 to 220 parts by mass, and particularly preferably 140 to 200 parts by mass. If the amount of fine aggregate is less than 100 parts by mass, the proportion of cement paste in the cement composition becomes too high, and the shape of the shaped object becomes easily distorted.If the amount of fine aggregate is more than 250 parts by mass, the proportion of fine aggregate in the cement composition becomes too high, and clogging occurs easily during pumping.
[0021] In the second embodiment of the cement composition of the present invention, which contains a coarse aggregate, a part of the fine aggregate in the first embodiment, which does not contain a coarse aggregate, is replaced with the coarse aggregate. By using the coarse aggregate, the material cost can be further reduced and the dimensional stability can be further improved. Examples of the coarse aggregate include river gravel, mountain gravel, land gravel, sea gravel, crushed stone, slag coarse aggregate, lightweight coarse aggregate, etc. These may be used alone or in combination of two or more. Among the coarse aggregates, crushed stone is preferred. The amount of coarse aggregate such as crushed stone relative to 100 parts by mass of cement is preferably 10 to 210 parts by mass, more preferably 40 to 190 parts by mass, and particularly preferably 70 to 170 parts by mass. The amount of fine aggregate corresponding to this amount of coarse aggregate is preferably 40 to 240 parts by mass, more preferably 60 to 210 parts by mass, and particularly preferably 80 to 180 parts by mass. If the amount of the coarse aggregate is less than 10 parts by mass, the proportion of mortar in the cement composition becomes large, and it is not possible to expect a reduction in material costs or a sufficient improvement in dimensional stability. If the amount of the coarse aggregate is more than 210 parts by mass, the proportion of the coarse aggregate in the cement composition becomes too large, and clogging is likely to occur during pumping.
[0022] In the present invention, the fibers are used to increase the bending strength and other properties of the cement composition. Examples of the fibers include organic fibers, metal fibers, glass fibers, carbon fibers, etc. These may be used alone or in combination of two or more. Examples of organic fibers include PVA fibers (polyvinyl alcohol fibers; also called "vinylon fibers"), polypropylene fibers, polyethylene fibers, aramid fibers, etc. Among them, PVA fibers and polypropylene fibers are preferred because they are high in strength, low in cost, and easy to obtain. Metal fibers include steel fibers.
[0023] The diameter of the fibers is preferably 0.005 to 1.0 mm, more preferably 0.02 to 0.8 mm, still more preferably 0.05 to 0.6 mm, still more preferably 0.1 to 0.5 mm, and particularly preferably 0.2 to 0.4 mm. If the diameter is 0.005 mm or more, the bending strength is greater. If the diameter is 1.0 mm or less, the length is not excessively large so that the aspect ratio (length / diameter) falls within a preferable range, and material separation is less likely to occur.
[0024] The length of the fibers is preferably 2 to 30 mm, more preferably 5 to 26 mm, further preferably 8 to 22 mm, further preferably 10 to 20 mm, and particularly preferably 12 to 18 mm. If the length is 2 mm or more, the bending strength is increased, and if the length is 30 mm or less, the aspect ratio (length / diameter) is within a preferable range and the length is not excessively large, so that material separation is unlikely to occur.
[0025] The aspect ratio (length / diameter) of the fibers is preferably 20-200, more preferably 25-150, further preferably 30-100, further preferably 35-80, and particularly preferably 40-60. When the aspect ratio is 20 or more, the bending strength is increased. When the aspect ratio is 200 or less, material separation is unlikely to occur.
[0026] The amount of fibers in the cement composition is 0.5 to 5.0 volume %, preferably 0.7 to 4.6 volume %, more preferably 0.9 to 4.2 volume %, and particularly preferably 1.1 to 3.8 volume %, based on 100 volume % of the total amount of the cement composition excluding the fibers. When the amount of the fibers in the cement composition is 0.5% by volume or more, the bending strength of the cement composition is increased. When the amount of the fibers in the cement composition is 5.0% by volume or less, the pot life of the cement composition can be extended.
[0027] The amount of water is 21 to 59 parts by mass, preferably 24 to 51 parts by mass, more preferably 27 to 43 parts by mass, and particularly preferably 30 to 35 parts by mass, relative to 100 parts by mass of cement. If the amount of water is less than 21 parts by mass, the viscosity of the cement composition is too high and it becomes difficult to pump, whereas if the amount of water is more than 59 parts by mass, the compressive strength of the cement composition is reduced.
[0028] The cement composition of the present invention may contain materials other than cement, urea, a set retarder, fine aggregate, coarse aggregate, fiber, and water, as necessary. Other materials include various admixtures such as air-entraining agents, water-reducing agents, air-entraining water-reducing agents, high-performance water-reducing agents, and high-performance air-entraining water-reducing agents, as well as various admixtures such as ground granulated blast furnace slag, silica fume, and calcium aluminates excluding alumina cement.
[0029] A method for producing a layered object using the cement composition of the present invention will now be described. The method for manufacturing an additive manufacturing object includes a pumping process in which the above-mentioned cement composition is pumped with a pump and supplied to an additive manufacturing device, and a modeling process in which the cement composition is extruded in the additive manufacturing device and additive manufacturing is performed layer by layer to produce an additive manufacturing object. The method for producing a layered object of the present invention can also include a composition production step of producing a cement composition as a pre-step of the pumping step. Each step will be described below.
[0030] [Composition manufacturing process] The composition production step is a step for producing a cement composition to be pumped in the next pumping step. In the composition production process, the means for producing the cement composition is not particularly limited, and a mixer generally used in mixing materials for producing mortar or concrete can be used. Specific examples include a vertical mixer, a horizontal mixer, a Nauter mixer, a tilting mixer, a forced mixer, and a twin-shaft mixer. Examples of vertical mixers include the "Hobart Mixer" manufactured by Hobart and the "Henschel Mixer" manufactured by Henschel. Examples of horizontal mixers include the "Lodige Mixer" manufactured by Lodige.
[0031] [Pressure transport process] The pressure-feeding step is a step of feeding the cement composition produced in the composition production step by a pressure-feeding pump such as a squeeze pump to an additive manufacturing device used in the next step, the modeling step. An example of the configuration of the pressure-feeding means in the pressure-feeding step is one in which a hopper, a squeeze pump, and a pressure-feeding pipe are connected in this order. The hopper has an opening at its upper part for pouring in the cement composition produced in the preceding composition production process, and has a discharge part at its lower part for supplying the cement composition contained in the hopper to a squeeze pump. The squeeze pump is a pump for pumping the cement composition to the additive manufacturing apparatus. As the squeeze pump, a commercially available pump for pumping mortar can be used. An example of the pressure-feeding pipe is a rubber hose. The length of the pressure-feeding pipe is, for example, 2 to 10 m. The inner diameter of the pressure-feeding pipe is, for example, 1 to 10 cm.
[0032] [Modeling process] The modeling step is a step of modeling a desired layered object while layering the cement composition supplied in the pressure-feeding step. An example of an additive manufacturing device used in the modeling process includes at least an additive manufacturing stage, a nozzle for supplying the cement composition pumped by a pressure pipe to the additive manufacturing stage, a nozzle position adjustment device that can move the nozzle two-dimensionally on a horizontal plane or move the nozzle vertically, and a control computer for controlling the additive manufacturing. In the additive manufacturing device, the cement composition is extruded and supplied from a nozzle that moves based on digital data from a control computer to a platform for additive manufacturing, and one layer of the cement composition is first modeled. Next, the nozzle moves upward by one layer and supplies one layer of the cement composition onto the already created one layer of the modeled object while moving horizontally, forming a two-layer modeled object in total. After that, the same operation is repeated to complete the desired additive manufacturing object. EXAMPLES
[0033] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. [Materials used] (1) Cement: A mixture of ultra-fast hardening cement (product name: Super Jet Cement; manufactured by Taiheiyo Cement Corporation) and ordinary Portland cement (manufactured by Taiheiyo Cement Corporation) in a 1:1 mass ratio. (2)Urea (3) Set retarder: citric acid (reagent) (4) Fiber: PVA fiber (diameter: 0.3 mm, length: 15 mm, aspect ratio: 50) (5) Fine aggregate: crushed limestone sand (6) Coarse aggregate: crushed stone 2005
[0034] [Production method of the first embodiment of the cement composition not containing coarse aggregate] (Examples 1 to 11, Comparative Examples 1 to 8) All the materials shown in Table 1 except for water were put into a Hobart mixer (volume: 15 liters) and mixed by stirring for 30 seconds. Water was then added and the mixture was kneaded for 4 minutes to produce cement compositions not containing coarse aggregate (Examples 1 to 11 in Table 1 and Comparative Examples 1 to 8 in Table 2).
[0035] [Method for producing a cement composition according to a second embodiment containing coarse aggregate] (Examples 12 to 14, Comparative Example 9) All the materials shown in Table 2 except for water were put into a pan mixer (volume: 55 liters) and mixed by stirring for 30 seconds. Water was then added, and the mixture was kneaded for 2 minutes and scraped off. After that, the mixture was kneaded again for 2 minutes to produce cement compositions containing coarse aggregate (Examples 12 to 14 and Comparative Example 9 in Table 2).
[0036] The produced cement composition of the first or second embodiment was used to carry out the following tests (a) to (b1) or (a) to (b2). (a) Visual evaluation of the extrudability of cement compositions Immediately after the above-mentioned 4 minutes of mixing, the cement composition of the first or second embodiment was fed by the pressure pump, and layer-by-layer modeling of the cement composition was performed using a layer-by-layer modeling device, and the extrudability of the cement composition extruded from the nozzle was visually evaluated. The results are shown in Table 1. If the cement composition was extruded continuously from the nozzle without causing material separation or clogging of the pressure-feeding pipe, the cement composition was evaluated as having extrudability that did not interfere with additive manufacturing, and the extrudability evaluation column in Table 1 was marked with a "O" (good). On the other hand, if the cement composition extruded from the nozzle separates into fibers and non-fiber materials, or into aggregate and other materials, causing discontinuous extrusion of the cement composition, or if the cement composition is not extruded from the nozzle, good extrudability of the cement composition cannot be ensured, and the cement composition is evaluated as unsuitable for additive manufacturing applications, and the extrudability evaluation column in Table 1 is marked with an "X."
[0037] (b1) Flow test for the first embodiment not including coarse aggregate (evaluation of the rate of decrease in flow value) The flow value (mm) of the cement composition immediately after 4 minutes of mixing in the production of the above-mentioned cement composition not containing coarse aggregate was measured when the composition was dropped 15 times in accordance with the method described in "JIS R 5201:2015 (Physical Testing Methods for Cement)" (hereinafter, also referred to as "flow value immediately after mixing"). The results are shown in Table 1. In addition, for the cement composition 90 minutes after adding water in the above-mentioned mortar production, the flow value (mm) (hereinafter also referred to as "flow value after 90 minutes") was measured in the same manner as the above-mentioned measuring method for "flow value immediately after mixing". The "flow value decrease rate" (%) was calculated using the following formula (1). The results are shown in Table 1. [Flow value decrease rate] (%) = ([Flow value immediately after mixing] - [Flow value after 90 minutes]) × 100 ÷ [Flow value immediately after mixing] (1) When the rate of decrease in the flow value is less than 30%, the good fluidity of the cement composition not containing coarse aggregate can be maintained for a long period of time, and a usable time that does not interfere with additive manufacturing can be ensured.
[0038] (b2) Test on the second aspect of the cement composition containing coarse aggregate (evaluation of the rate of decrease in flow value of the mortar part obtained by wet screening) In the production of the cement composition containing the above-mentioned coarse aggregate, the coarse aggregate was separated from the cement composition immediately after 4 minutes of mixing and from the cement composition 90 minutes after adding water using a mesh sieve with a nominal opening of 4.75 mm as specified in "JIS Z 8801-1 (metal mesh sieves)". The flow values (mm) of the obtained mortar portion ("flow value immediately after mixing" and "flow value after 90 minutes") after 15 drops were measured in accordance with the method described in "JIS R 5201:2015 (Physical test methods for cement)", and the same evaluation as in (b1) above was performed. The results are shown in Table 2.
[0039] [Table 1]
[0040] [Table 2]
[0041] As shown in Tables 1 and 2, in Examples 1 to 14, good extrudability was obtained. Moreover, in Examples 1 to 14, the rate of decrease in flow value was less than 30%, and it was found that the pot life was sufficient for additive manufacturing. On the other hand, in Comparative Example 3, in which the amount of the setting retarder used exceeded 2.0 parts by mass, and Comparative Example 6, in which the amount of urea used was less than 0.5 parts by mass, material separation occurred and the materials were unsuitable for additive manufacturing. In addition, in Comparative Example 4, in which the amount of fine aggregate used exceeded 250 parts by mass, in Comparative Example 5, in which the amount of fiber used exceeded 7.0 volume %, and in Comparative Example 9, in which the amount of fine aggregate used was less than 40 parts by mass, blockage occurred in the pressure pipe, and the cement composition was not extruded from the nozzle. Furthermore, in Comparative Example 2, in which the amount of urea used was less than 0.5 parts by mass, and in Comparative Example 7, in which the amount of set retarder used was less than 0.5 parts by mass, the extrudability of the cement composition was good, but the pot life of the cement composition was short. Furthermore, in Comparative Example 1, in which the amount of water used was less than 27 parts by mass, and in Comparative Example 8, in which the amount of fine aggregate used was less than 100 parts by mass, the viscosity of the cement composition was too high, and both the extrudability and the pot life of the cement composition were inadequate.
Claims
1. A cement composition comprising cement, urea, a set retarder, fine aggregate, fiber, and water, and no coarse aggregate, The amount of the urea is 0.5 to 15 parts by mass, the amount of the retarder is 0.5 to 2.0 parts by mass, the amount of the fine aggregate is 100 to 250 parts by mass, and the amount of the water is 21 to 59 parts by mass, relative to 100 parts by mass of the cement; A cement composition characterized in that the ratio of the fibers in the cement composition is 0.3 to 7.0 volume % in terms of an external ratio relative to 100 volume % of the entire cement composition excluding the fibers.
2. A cement composition comprising cement, urea, a set retarder, fine aggregate, coarse aggregate, fiber, and water, With respect to 100 parts by mass of the cement, the amount of the urea is 0.5 to 15 parts by mass, the amount of the setting retarder is 0.5 to 2.0 parts by mass, the amount of the fine aggregate is 40 to 240 parts by mass, the amount of the coarse aggregate is 10 to 210 parts by mass, and the amount of the water is 21 to 59 parts by mass, A cement composition characterized in that the ratio of the fibers in the cement composition is 0.3 to 7.0 volume % in terms of an external ratio relative to 100 volume % of the entire cement composition excluding the fibers.
3. 3. The cement composition according to claim 1 or 2, wherein the cement comprises an ultra-fast hardening cement.
4. The cement composition according to any one of claims 1 to 3, wherein the fibers have a diameter of 0.005 to 1.0 mm, a length of 2 to 30 mm, and an aspect ratio (length / diameter) of 20 to 200.
5. A method for producing a layered object using the cement composition according to any one of claims 1 to 4, A pumping step of pumping the cement composition to supply it to an additive manufacturing apparatus; and a modeling step of extruding the cement composition in the layer-by-layer modeling apparatus to produce a layer-by-layer modeled object; A method for manufacturing a layered object, comprising:
Citation Information
Patent Citations
Self-recovery concrete admixture, method for manufacturing the same and self-recovery concrete material using the admixture
JP2012153577A
Additional production method
JP2018122539A
Hydraulic composition for addition manufacturing device, and manufacturing method of cast
JP2019116095A
Manufacturing method of fiber reinforced concrete member
JP2020002744A
Molding cement composition
JP2020066549A